The Effect of Covid-19 Pandemic on Local Government Performance in Service Delivery. A Case Study of Kabale District Local Government. - Musinguzi, Joshua (Kabale University, 2023)
The study investigated the effect of the Covid-19 pandemic on local government performance in service delivery. A case study of Kabale district local government, Uganda. The study was guided by the following objectives namely; to find out the effect of covid-19 on service delivery. co identify the challenges that local governments faced during COVID-19 amidst service delivery, and to identify the strategies that local governments are using in mitigating the effects of COVID-19 on local government performance in service delivery in Kabale district. The study also considered a sample size of 66 respondents. Data was collected through questionnaire and interviewing methods, these methods gave accurate and reliable information. The findings to a larger extent showed that the lockdown and other related SOPs affected employee turn-up in local governments. Some respondents also showed that to a large extent, the Central Government (CG) has taken on the bulk of the responsibility for managing the spread of the disease and provision of other services, meaning to a smaller extent COVID-19 has affected service delivery as far as taking the responsibility of central government into the lower local government. Despite advances in political freedoms, many developing countries have contexts that constrain their work and operation during COVID-19, therefore there is a need to Put in place a local economic recovery task force in each local government Uganda's government has limited financial resources, which is a component for service delivery, lower local governments are faced with demands for improving service delivery, but consumers of the services are very reluctant to pay more. The government should provide soft loans to business operators like Emyooga such that the businesses can be implemented hence bringing service nearer to the people and this in turn will increase the tax revenue of the government helping to meet other services like education in the district. The study concludes that Covid-19 has had a profound impact on our society, which should not be understated. Many lives have been lost, and the social and economic impact will be felt for some time to come. In every crisis, however. there is opportunity. The study recommends that tailored approaches are needed, recognizing the diverse effects of lockdowns according to young people's gender, age, stage of education, socioeconomic status, and location (rural, peri-urban, and urban). Provide additional economic support: As well as ensuring access to food for all, in low-income settings governments could consider some form of immediate cash transfer for young people and families.